Androgen modulation of social decision-making mechanisms in the brain: an integrative and embodied perspective - Oliveira, Gonçalo A.; Oliveira, Rui F. (Frontiers in Neuroscience, 2014)
Apart from their role in reproduction androgens also respond to social challenges and this response has been seen as a way to regulate the expression of behaviour according to the perceived social environment (Challenge hypothesis, Wingfield et al. 1990). This hypothesis implies that social decision-making mechanisms localized in the central nervous system (CNS) are open to the influence of peripheral hormones that ultimately are under the control of the CNS through the hypothalamic-pituitary-gonadal axis. Therefore, two puzzling questions emerge at two different levels of biological analysis: (1) Why does the brain, which perceives the social environment and regulates androgen production in the gonad, need feedback information from the gonad to adjust its social decision-making processes? (2) How does the brain regulate gonadal androgen responses to social challenges and how do these feedback into the brain? In this paper, we will address these two questions using the integrative approach proposed by Niko Tinbergen, who proposed that a full understanding of behaviour requires its analysis at both proximate (physiology, ontogeny) and ultimate (ecology, evolution) levels.